PEMANFAATAN KOLANG-KALING BUAH AREN DAN NANAS (Ananas Comosus L. Merr.) DALAM PEMBUATAN SLICED JAM - Sabrina Berta; Teltje Koapaha; Lucia Mandey (COCOS, 2017)
ABSTRACK The objective of this research is to know the level of panelist's fondness for sliced jam of kolang-kaling and pineapple and to determine the exact percentage of kolang-kaling and pineapple to the chemical properties of slice jam. The design used in the study was Completely Randomized Design with percentage of pineapple-compatible (60%: 40%, 50%: 50%, 40%: 60%), and each treatment was repeated 3 times. The observations included the test of favorite level, moisture content, total sugar, and crude fiber. The results of sliced jam and pineapple studies obtained by treatment of 40% pulp-kaling and 60% pineapple (treatment A) were the most preferred percentages by including: aroma, color, flavor and texture as well as getting the average value rather like with chemical characteristics that is water content 28.11%, total sugar 47.93%, and crude fiber 0.01%. Keywords: Sliced jam, Kolang-kaling, and Pineapple.